Information availabilities of the thermal radiation noise (Analytical overview) - Salkov, E.A.; Svechnikiv, G.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The main purpose of this overview is to make an effort at joining the widely spread practical tendency of “damping the noise” with the non-apparent but presumably perspective thesis “using the noise” through the realization of “information properties of noise”. The paper deals with physical peculiarities of the equilibrium thermal radiation, which have been considered within the black body model for the case of ultimate restrained photon flows inside an ideal (“lossless”) optical communication channel. Restrictions connected with the uncertainty relations have been used to determine critical interrelations between the thermal radiation parameters and the sizes of the thermal radiator and the ideal photodetector. The conception of the “intrinsic micro-amounts of chaos” has been proposed, and its usefulness was discussed. Principle feasibility has been considered for a distant identification of a small-sized thermal radiator by means of detecting its thermal radiation. A single small-size radiator has been phenomenologically treated within the black body model. It has been shown that it is possible to obtain a quantitative evaluation of the temperature and the size of a small-size radiator through measurement of the thermal radiation fluctuations in case when the optical image of the radiator is unavailable.